New monoclonal antibody specific for a 6.5 kDa glycoprotein which presents mainly on a B cell of chronic lymphocytic leukemia (CLL) - (:unkn) unknown (ELSEVIER SCIENCE BV, 2001)
Chronic lymphocytic leukaemia (CLL) is a most common form of adult leukemia. No specific marker for CLL has been defined until today. We attempt to produce a specific monoclonal antibody (mAb) to CLL B cells. For this purpose, Balb-C mice were immunised with peripheral blood lymphocytes of a patient with CLL. After the fusion, the immunised mouse spleen cells and SP2/0 myeloma cell line, antibody secreting clones were selected by ELISA and specific antibody was determined by flow cytometry. Leukemic cells from different patients, different cell line and lymphoid tissue were tested with this mAb using how cytometry and immunoperoxidase methods. Ligand of the mAb on cell surface was identified using epitope analysing method. We have shown that this mAb is specific to a molecule with 6.5 kDa molecular weight, which is present mainly on B CLL cells (63.7 +/- 16.4%). It has also been shown that this molecule was a glycoprotein. Amongst the different cell lines that were tested, Raji cell, Molt-3 and P3HR-1 cells were expressing this molecule. We, therefore, suggest that it is a novel molecule with unknown function and is mainly present on the B cells of CLL. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: B-cell; CLL; novel monoclonal antibody; MER; CD5; ANTIGENS; ROSETTES